Pengaruh kebijakan dividen dan Earning Per Share (EPS) terhadap Price to Book Value pada perusahaan makanan dan minuman yang terdaftar di Bursa Efek Indonesia - Christine Herawati Limbong; Mulya Rafika; Yudi Prayoga; Bhakti Helvi Rambe; Eva Fitria (Proceeding of National Conference on Accounting & Finance, 2021)
The purpose of this study was to determine the effect of earnings per share and dividend policy on price to book value partially on food and beverage companies on the Indonesia Stock Exchange. To find out whether the debt to equity ratio moderates the relationship between earnings per share and dividend policy on price to book value partially on food and beverage companies on the Indonesia Stock Exchange. The number of samples in this study amounted to 12 companies during the study period of 5 years so that it has 60 observational data. The analysis technique used is multiple linear regression. The results showed that Dividend policy has a significant effect on price to book value. Earnings per share had no significant effect on price to book value. Together earning per share variable and dividend policy has a significant affect the price to book value.